Análise dos processos de integração interfuncional em organizações orientadas para o mercado : um estudo na Costa Rica e no Brasil - Oviedo, Ana Beatriz Murillo (2016)
Market orientation is a strategic perspective looking for knowledge generation and dissemination about context, to satisfy market needs. This market needs satisfaction must be searched through responsive strategies, involving the participation of several functions and hierarchical levels for the generation of market intelligence. Hence, market orientation occurs through interfunctional processes looking for attending market needs through information obtained from: competitors, consumers, customers, shoppers and suppliers. On the other hand interfunctional integration is about the efforts and tasks with active participation of many functions or departments of an organization, looking for the generations of improving results through perceptions union with formal and informal integration factors. Literature shows interfunctional integration as an antecedent for market orientation, and a list of nine market oriented integration factors. Nevertheless, these studies do not show how interfunctional integration is operationalized in the organizations in order to achieve market orientation. This research has the objective of analyzing how interfunctional integration process helps organizations to adopt market orientation strategies, on the Latin American Foods Industrial Sector. To do this, a Multi-Case study was conducted in Costa Rica and Brazil, with two market oriented firms. A total of 24 in depth interviews were realized between June and October 2016, with managers and supervisors from diverse departments such as marketing, commercial, logistics, finance and human resources. Moreover, for triangulation, integration level of the organizations was evaluated though a quantitative scale. Results show that both organizations have market oriented integration processes, as contact points involving more than three departments, to improve responsiveness. These processes are: innovation launch, products and service delivery, claims solution and innovation and improvements projects for a stronger market orientation. These processes require integration factors to help the achievement of results related to market orientation: responsiveness, market intelligence dissemination and customer satisfaction. Seven theoretical propositions are presented, with the aim of increasing elements to the knowledge of the operationalization of market orientation on organizations, through interfunctional integration.